Trust in Robots - Koeszegi, Sabine T.; Vincze, Markus (TU Wien Academic Press, 2022)
Robots are increasingly becoming prevalent in our daily lives within our living or working spaces. We hope that robots will take up tedious, mundane or dirty chores and make our lives more comfortable, easy and enjoyable by providing companionship and care. However, robots may pose a threat to human privacy, safety and autonomy; therefore, it is necessary to have constant control over the developing technology to ensure the benevolent intentions and safety of autonomous systems. Building trust in (autonomous) robotic systems is thus necessary. The title of this book highlights this challenge: "Trust in robots-Trusting robots". Herein, various notions and research areas associated with robots are unified. The theme "Trust in robots" addresses the development of technology that is trustworthy for users; "Trusting robots" focuses on building a trusting relationship with robots, furthering previous research. These themes and topics are at the core of the PhD program "Trust Robots" at TU Wien, Austria.